Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Khusus (DAK), dan Belanja Daerah Terhadap Tingkat Kemiskinan (Studi Kasus 35 Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2012-2016) - Nur Ika Fitriyanti; Herniwati Retno Handayani (Universitas Diponegoro, 2020)
The purpose of this study is to analyze the influence of Local Revenue (PAD), Special Allocation Fund (DAK), and Region Expenditure to Poverty Rate at Regency/City in the Province Central Java Year 2012-2016. This study use secondary data. The method used to analyze is pooled data regression. Pooled data is a combination of cross section data that includes 35 Regency/Cities of Central Java and time series data from 2012 until 2016. The result showed that Fixed Effect Model (FEM) is the most appropiate. Based on regression result of this study shows that Local Revenue (PAD) and Special Allocation Fund (DAK) have negative significant effect to decrease of Poverty Rate. While Region Expenditure has a negative and not significant effect on the Poverty Rate. Simultaneosly, Local Revenue (PAD), Special Allocation Fund (DAK), and Region Expenditure have significant effect to Poverty Rate.